2022
DOI: 10.3389/fgene.2021.793182
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of the CircRNA-Based ceRNA Network in Renal Fibrosis Induced by Ischemia Reperfusion Injury

Abstract: Background: Circular RNAs (circRNAs), which have broad posttranscriptional regulatory potencies, are involved in the pathogenesis of fibrotic diseases and are promising diagnostic biomarkers and therapeutic targets. However, their specific roles in renal fibrosis remain elusive.Methods: A robust unilateral renal ischemia reperfusion injury (UIRI) mouse model was established to recapitulate the pathophysiology of renal fibrosis. The expression of circRNAs, miRNAs, and mRNAs was profiled by high-throughput RNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
(43 reference statements)
2
5
0
Order By: Relevance
“…The differential circRNA was significantly related to ECM–receptor interaction, Arrhythmogenic right ventricular cardiomyopathy (ARVC), Thyroid hormone synthesis, and Proteoglycans in cancer and Focal adhesion. CircRNA could combine with miRNA in a targeted way and indirectly regulate the translation of mRNA 27 . The miRanda software was used to select the differentially expressed circRNA to predict the target miRNA, and the circRNA–miRNA network diagram was drawn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential circRNA was significantly related to ECM–receptor interaction, Arrhythmogenic right ventricular cardiomyopathy (ARVC), Thyroid hormone synthesis, and Proteoglycans in cancer and Focal adhesion. CircRNA could combine with miRNA in a targeted way and indirectly regulate the translation of mRNA 27 . The miRanda software was used to select the differentially expressed circRNA to predict the target miRNA, and the circRNA–miRNA network diagram was drawn.…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are few research articles on the relationship between circRNA and urethral stricture. The existing literature mainly focuses on renal fibrosis 20 , 27 . Other studies have found that circRNA is related to the mechanism of keloid formation 29 31 .…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput RNA sequencing (RNA-Seq) has made it possible to identify thousands of circRNAs involved in physiological processes and in the pathogenesis of various diseases [ 78 , 79 , 80 , 81 , 82 ]. The most commonly used way to detect differentially expressed circRNAs (DECs) includes a comparative analysis of their representation in experimental and control biological samples using microarrays or RNA-Seq.…”
Section: Main Approaches For Studying the Role Of Circrna In The Path...mentioning
confidence: 99%
“…In another study of unilateral IRI murine kidney model 4983 circRNAs were found to be differentially expressed, and bioinformatic analysis showed that the parental genes of these circRNAs were involved in focal adhesion, adhesion junctions, and the regulation of actin cytoskeleton pathways. Two hub genes, namely, circ-SLC8A1 (mmu_circ_0000823) and circ-APOE (mmu_circ_0014064), were associated with a large number of differentially expressed miRNAs and mRNAs on bioinformatic analysis [ 51 ]. These circRNAs are also aberrantly expressed in other conditions such as solid organ tumours and CKD, where they are associated with cell proliferation, angiogenesis, cell migration, and epithelial-to-mesenchymal transition including in the induction and propagation of renal fibrosis.…”
Section: Circrna Expression In Aki Due To Ischaemia-reperfusion Injurymentioning
confidence: 99%